Effect of a single meloxicam administration on newborn Holstein–Friesian dystocia calves: Field results from the first 10 days of life - Fabian Kunz; Sait Sendag; Mehmet Yildiz; Klaus Failing; Axel Wehrend (Veterinary World, 2022)
Background and Aim: Calves have increased morbidity and mortality rates after dystocia. One cause is pain during birth, which reduces their colostrum intake. The administration of nonsteroidal anti-inflammatory drugs (NSAIDs) may break this causality. This study aimed to determine the consequences of a single administration of the NSAID meloxicam to dystocia calves after birth.